Palatal Lift Appliance in a Case of Palatal Incompetence Secondary to Motor Neurone Disease. (1st January 2021) - Daly, Alex
Abstract : Velopharyngeal deficiencies are challenging conditions to manage, often requiring input from a number of different specialties including restorative dentistry. Palatal incompetence, that is, the inability of a structurally intact palate to elevate and close the nasopharynx from the oropharynx can result in hypernasality and air escape, compromising speech sounds as well as causing swallowing difficulty. The palatal lift appliance is a prosthesis designed to elevate the palate to aid velopharyngeal closure, and has been used to manage patients with neurological disorders affecting the palate. This report presents such management in a patient with motor neurone disease. CPD/Clinical Relevance: Dentists should be integral in the management of patients with motor neurone disease to help maintain oral health and prevention of dental disease, but also to provide speech prostheses and liaise with speech and language therapists. Patients with motor neurone disease may present to a generalist for routine dental care, and GDPs should be aware of the challenges of managing the dental work for this group of people.